Bulk density and water tensions in the soil on corn root production - João A. S. Nunes; Edna M. Bonfim-Silva; Tonny J. A. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Inadequate management of soil and water can cause changes in soil physical characteristics, resulting in lower root development. Thus the objective of the present study was to evaluate the dry matter production of corn roots under combinations of levels of bulk density and water tension in the soil. The experiment was conducted in a greenhouse in a randomized block design, based on a modified central composite design of a 52 fractional factorial scheme, of combinations of bulk densities (1.0, 1.2, 1.4, 1.6 and 1.8 Mg m-3) and water tensions in the soil (10, 20, 30 40 and 50 kPa), resulting in 13 treatments with four replicates. An Oxisol collected in the layer of 0-0.2 m was used. The pots were made of PVC (polyvinyl chloride) tube with compacted soil in the middle layer. The tensiometers were installed at a depth of 0.15 m, remaining in the central region of the compacted layer. The experiment was collected 104 days after sowing. Root dry matter production of corn was limited by increased water stress and bulk density.